Pengaruh Sosial, Pribadi, & Psikologi terhadap Keputusan Pembelian di Shopee dengan Penipuan sebagai Variabel Moderasi - Larasati, Devi (Jurnal Ilmiah Poli Bisnis, 2022)
This study aims to determine the effect of social, personal, and psychological factors on purchasing decisions at Shopee with fraud as a moderating variable. This study uses a quantitative approach. With the SEM-PLS research method using the SmartPLS 3.0 software. In this study, the population was the management study program students of the University of Muhammadiyah Gresik batch 2018 with a sample of 137 respondents. The sampling technique used a purposive sampling method. This study uses primary data that contains respondents' answers to questionnaires that have been distributed via google form. The results show that: 1) Social factors have a positive and significant effect on purchasing decisions at Shopee, 2) Personal factors have no significant effect on purchasing decisions at Shopee, 3) Psychological factors have a positive and significant effect on purchasing decisions at Shopee, 4) Fraud can be a moderating variable and weaken social factors on purchasing decisions, 5) Fraud is not able to be a moderating variable for personal factors in purchasing decisions, 6) Fraud is not able to be a moderating variable for psychological factors in purchasing decisions.